Flowering induction period, yield and quality of pineapple - Choairy, Salim Abreu (Pesquisa Agropecuaria Brasileira, 2014)
The effects of the flowering induction period on the production and quality of pineapple (Ananas comosus Mill.), cv. Smooth Cayenne were studied in Mari county, State of Paraíba, Brazil. The results obtained show the possibility of fruit production year around, without great losses of fruit quality. During the rainy season, fruit yield and weight increased; a greater brix/acidity ratio was obtained in months with lower rainfall. Precocious flowering induction during dry periods resulted in imperfect and fasciated fruits, while greater number of slips was obtained with late induction.